Expert ASP.NET 2.0 Advanced Application Design - Selly, Dominic (Apress, 2012)
Microsoft has been working on version 2.0 of the.NET Framework and Visual Studio 2005 for a number of years now. Between the bits that were handed out at the PDC in 2003 and the release candidate handed out at the PDC in 2005, there’s been an unusually long period of time for curious developers to play around with the new functionality, picking out their favorites, and pining for the day they can be used in a production application. Over that same period of time the features have changed quite a bit. It was also an unusually long period of time for Microsoft’s customers to provide feedback about what worked and what didn’t, and what should be changed or preserved before putting the bits into production. What has resulted is an impressive set of functionality that should be a boon to any development effort. Because of the long period of time that some version of “Whidbey” (as it was code-named during the development process) has been available, many folks have been able to play with the features of this new version, and even more have seen demonstrations of these features at conferences, in magazines, and online. At its time of release, the development environment provided by the .NET Framework version 2.0 and Visual Studio .NET 2005 might be the most broadly familiar “new” product ever released.)